THE INFLUENCE OF TRAINING AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE THROUGH INCENTIVES AMONG HR STAFF AT DR. SAIFUL ANWAR REGIONAL PUBLIC HOSPITAL, EAST JAVA PROVINCE - Handriasti Handriasti; Moch Natsir; Harianto Respati; Elevenson Nadapdap (Adisam Publisher, 2025)
This study aims to examine the effect of training and work discipline on employee performance through incentives as an intervening variable among the Human Resources (HR) staff at Dr. Saiful Anwar Regional Public Hospital, East Java Province. The background of the research highlights the challenges in public health institutions where training often becomes a formality and work discipline issues such as absenteeism and procedural violations remain prevalent. A quantitative research method was applied, involving 165 HR employees as respondents. Data were collected through questionnaires and analyzed using path analysis. The results show that both training and work discipline have a direct positive and significant effect on employee performance. Furthermore, incentives play a mediating role, strengthening the influence of training and discipline on performance. These findings suggest that effective training, strong work discipline, and fair incentive systems create a synergistic impact in enhancing employee performance. This study provides managerial insights for hospital management to optimize human resource strategies in order to improve service quality and operational efficiency.